Methybacterium symbioticum e adubação nitrogenada em milho e cevada - Gallina, Alessandra (2025)
Barley (Hordeum vulgare) and maize (Zea mays) require a significant amount of nitrogen throughout their development cycle. Although essential, the processes involved in the production of nitrogen fertilizers demand high energy inputs and lead to the emission of greenhouse gases. In addition, they are subject to losses through volatilization and leaching. As a result, microbial alternatives for biological nitrogen fixation have been sought, among them Methylobacterium symbioticum SB23, a new bacterial strain. The objective of this study was to evaluate possible changes in the growth and grain yield of maize and barley under different topdressing nitrogen rates combined with foliar application of Methylobacterium symbioticum. Four experiments were conducted: two with maize (in Coxilha–RS and Carazinho–RS) and two with barley (in Espumoso–RS, 2023, and Coxilha–RS, 2024). Different nitrogen doses were assessed for each crop, with or without foliar application of Methylobacterium symbioticum. Evaluated variables included physiological traits, such as photosynthetic activity and chlorophyll content; morphological traits, such as plant height and stem diameter; and productive traits, including fresh biomass, dry biomass, and grain yield. There was no interaction between the bacterium and nitrogen doses for any of the variables assessed in maize and barley. Results indicated that nitrogen supply enhances the photosynthetic activity of barley plants, positively affecting their morphological and productive components. Methylobacterium symbioticum improved the photosynthetic activity in the BRS Cauê cultivar and increased chlorophyll content and biomass in ABI Valente plants. Foliar application of Methylobacterium symbioticum can promote increases in grain yield, chlorophyll content, plant height, and stem diameter in maize.